Overview of household solid waste recycling policy status and challenges in Malaysia - Moh, Yiing Chiee; Abd Manaf, Latifah (Elsevier, 2014)
With the annual increase in waste generation and heavy reliance on landfilling as disposal, method in Malaysia, it is just a matter of time before significant problems of space limitations, health, and environmental issues hit the nation severely. This paper attempts to develop an overview on solid, waste recycling in Malaysia at the most basic level of a community or nation which is the household, unit. Households are the main primary source of municipal solid waste in Malaysia, consisting of, recyclable materials at most 70% to 80% of the total waste composition as found placed in the, landfills. Overview on the existing household solid waste recycling policy and program status in, Malaysia is relevant in enhancing solid waste management measure from recycling perspective. Despite the high potential and opportunities for solid waste recycling, wastes are still simply being, dumped in an open area of ground without any attempt for recovery and recycling. Comparing to, recycling rates of neighboring countries, Malaysia is falling back at merely 5% which proves how, uncommon recycling practice is. The government is committed to significantly improve the national's, solid waste management services especially in waste minimization. Fortunately the emphasis on, recycling as a sustainable waste management strategy has taken a shift in paradigm as wastes, separation and recycling are part of the major changes in the current policy implementation. With, issues and challenges in recycling practice that were highlighted in this context especially from the, aspects of information availability and other loopholes within solid waste management policies and, related recycling program within the community, the question on whether the goals in 2020 can be, met remains unsure of but there is a possibility for a successful implementation of sustainable solid, waste management particularly in recycling.